Case Report: Allogenic Simple Limbal Epithelial Transplantation From a Human Leukocyte Antigen-Matched Living Related Donor to Treat Bilateral Corneal Chemical Burns Post Laser-Assisted in situ Keratomileusis - Chang, Yuh-Shin; Chan, Tsung-Yueh; Jan, Ren-Long; Tseng, Sung-Huei (Frontiers in Medicine, 2022)
A 35-year-old woman who had undergone laser-assisted in situ keratomileusis in both eyes experienced bilateral total limbal stem cell deficiency (LSCD) due to chemical burns. Due to bilateral severe LSCD, allogenic simple limbal epithelial transplantation (SLET) from a human leukocyte antigen (HLA)-matched living related donor was the first choice of treatment for her left eye. We report the first case of HLA or ABO matching living related allogenic SLET for permanent restoration of the cornea for bilateral LSCD treatment. Our ABO-HLA-matched living related allogenic SLET alleviation of the systemic immunosuppressant to topical corticosteroids alone. It also came the limitations of prolonged systemic immunosuppressant usage in conjunctival-limbal allografts and keratolimbal allograft.